FLUOROMETRIC EVIDENCE FOR DIFFERENT STOICHIOMETRIES FOR THE Na+/Mg2+ EXCHANGE IN Mg LOADED RAT THYMOCYTE - Contreras Jurado, Silvia Constanza; González Martínez, Marco T.; Cobos, Enrique J.; Soler Diaz, Agatángelo (My University, 2021)
The regulation of the cytosolic free magnesium concentration ([Mg2+]i) is a fundamental cellular process that requires magnesium extruding mechanisms. Here, we present evidence indicating that rat thymocytes are endowed with different Na/Mg exchange systems. Fluxes of magnesium were measured using the fluorescent magnesium indicator magfura-2. Cells were loaded with magnesium using the calcium ionophore A-23187 to 0.6- 8.0 mM [Mg2+]i (resting [Mg2+]i = 0.38 ± 0.06 mM, n = 5). The presence of extracellular sodium was required for magnesium exit. The initial rate of [Mg2+]i was stimulated by extracellular sodium with Michaelis-Menten kinetics. The Vmax of the sodium-dependent magnesium exit was markedly increased by [Mg2+]i. Holding the membrane potential at either ¿84 mV or at ¿10 mV had different effects on the sodium-stimulated magnesium efflux, depending on the extracellular sodium concentration ([Na+ ]o). At 10-30 mM [Na+ ]o, the magnesium efflux was faster at ¿10 mV than at ¿84 mV. Conversely, at 50-200 mM [Na+ ]o, the efflux of magnesium was faster at ¿84 mV that at ¿10 mV. At 75 mM [Na+ ]o, the activities where nearly the same at both membrane potential values. These observations suggest that the stochiometry of the Na+ /Mg2+ exchange changes with [Na+ ]